Noninsulin Antidiabetic Drugs for Patients with Type 2 Diabetes Mellitus: Are We Respecting Their Contraindications? - Irene Ruiz-Tamayo; Josep Franch-Nadal; Manel Mata-Cases; Dídac Mauricio; Xavier Cos; Antonio Rodriguez-Poncelas; Joan Barrot; Gabriel Coll-de-Tuero; Xavier Mundet-Tudurí (Journal of Diabetes Research)
Aim. To assess prescribing practices of noninsulin antidiabetic drugs (NIADs) in T2DM with several major contraindications according to prescribing information or clinical guidelines: renal failure, heart failure, liver dysfunction, or history of bladder cancer. Methods. Cross-sectional, descriptive, multicenter study. Electronic medical records were retrieved from all T2DM subjects who attended primary care centers pertaining to the Catalan Health Institute in Catalonia in 2013 and were pharmacologically treated with any NIAD alone or in combination. Results. Records were retrieved from a total of 255,499 pharmacologically treated patients. 78% of patients with some degree of renal impairment (glomerular filtration rate (GFR) < 60 mL/min) were treated with metformin and 31.2% with sulfonylureas. Even in the event of severe renal failure (GFR < 30 mL/min), 35.3% and 22.5% of patients were on metformin or sulfonylureas, respectively. Moreover, metformin was prescribed to more than 60% of patients with moderate or severe heart failure. Conclusion. Some NIADs, and in particular metformin, were frequently used in patients at high risk of complications when they were contraindicated. There is a need to increase awareness of potential inappropriate prescribing and to monitor the quality of prescribing patterns in order to help physicians and policymakers to yield better clinical outcomes in T2DM.